Phenotypic Profiling of Selected Cellulolytic Strains to Develop a Crop Residue-Decomposing Bacterial Consortium - Arman Shamshitov; Egidija Satkevičiūtė; Francesca Decorosi; Carlo Viti; Skaidrė Supronienė (Microorganisms)
Slow decomposition rates of cereal crop residues can lead to agronomic challenges, such as nutrient immobilization, delayed soil warming, and increased pest pressures. In this regard, microbial inoculation with efficient strains offers a viable and eco-friendly solution to accelerating the decomposition process of crop residues. However, this solution often focuses mostly on selecting microorganisms based on the appropriate enzymic capabilities and neglects the metabolic versatility required to utilize both structural and non-structural components of residues. Therefore, this study aimed to address these limitations by assessing the metabolic profiles of five previously identified cellulolytic bacterial strains, including Bacillus pumilus 1G17, Micromonospora chalcea 1G49, Bacillus mobilis 5G17, Streptomyces canus 1TG5, and Streptomyces achromogenes 3TG21 using Biolog Phenotype Microarray analysis. Moreover, this study evaluated the impact of wheat straw inoculation with single strains and a bacterial consortium on soil organic carbon and nitrogen content in a pot experiment. Results revealed that, beyond the core subset of 12 carbon sources, the strains exhibited diverse metabolic capacities in utilizing 106 carbon sources. All strains demonstrated effective straw biomass degradation compared to the negative control, with significant differences detected only in oil seed rape straw biodegradation estimations. Furthermore, wheat straw inoculated with a bacterial consortium showed a significant increase in soil organic carbon content after 180 days in the pot experiment. Overall, these findings underscore the critical role of metabolic profiling in gaining a deeper understanding of microbial capabilities and addressing the complexities of residue composition and environmental variability.